Development of cluster approach in tourism (Russia case study) - Rukomoinikova, Vera; Polukhina, Ann (Journal of Applied Engineering Science, 2016)
The concept of tourism clustering is currently in the focus of tourism development on national and regional levels. The research is based on international academic literature review and the analysis of Russian experience. The paper analyses the dynamics of the tourism potential of the partner regions joined into the cluster “Velikaya Volga” (The Big Volga), based on the expert opinion. There is a cost-benefit analysis of the tourism industry in the regions included into the tourism cluster using statistical data. The analysis-based diagrams show the differentiation of the Volga regions in terms of tourism potential use. Econometric approach allowed studying the dependence of tourism potential indicators on the tourism cluster “Velikaya Volga” revenue. The results of the research allow grouping the regions included in the cluster depending on the efficiency of their tourism potential implementation. The research also shows the significance of the comparative evaluation of tourism cluster potential. The comparative method used for the cluster analysis allows enhancing the development of the regional tourism.